An Investigation on Speed Control of a Spindle Cluster Driven by Hydraulic Motor: Application to Metal Cutting Machines - Ngoc Hai Tran; Cung Le; Anh Dung Ngo (International Journal of Rotating Machinery)
In this article, we present an experimental study on the speed stability of a spindle driven by a hydraulic motor, which is controlled by a proportional valve, through a V-belt transmission. The research includes the dynamic modeling of the transmission cluster and the transmission from the hydraulic motor to the working shaft via V-belt mechanism, together with the establishment of a mathematical model and fuzzy self-tuning PID controller model. In the model, the V-belt is assumed as an elastic module, and the friction coefficient and mass inertia moment of the hydraulic motor are considered as constant. The Matlab software is used to simulate the speed response of the hydraulic motor to the working shaft. Based on theoretical study, we resemble the experimental system and determine the parameters for the fuzzy self-tuning PID controller. We conduct experiment and investigate the speed stability of the working shaft from 300 to 1100 (rpm) based on transient response parameters such as the time delay, the setting time, the overshoot, and the rotation error at steady state. Thereby, in this study, the simulation and the experiment results are compared and evaluated regarding the speed stability of the working shaft driven by hydraulic motor transmitted through V-belt mechanism. The findings show the speed controllability by using proportional valve to manipulate the oil flow and applying a self-tuning PID controller to achieve very good results such as the error difference of 0.001 to 0.036%, the delay of 0.01 to 0.02 seconds, no overshoot, and the settling error less than 5% compared to the set values. On the other hand, we include the effect of the oil temperature of 40 to 80°C on the working shaft speed (500, 900 rpm) in this study and derive that the system works well at temperature range of 40 to 70°C. On these findings, we propose the applicability of this system on the current machinery cutters. In addition, we verify the effects of the hydraulic drive for main shaft, controlled by fuzzy PID, by comparison of the roughness of the machining work piece with respect to the one using the 3-phase motor drive.